2010
DOI: 10.1016/j.jcrs.2009.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravitreal triamcinolone acetonide injection on central macular thickness in diabetic patients having phacoemulsification

Abstract: Intravitreal injection of triamcinolone reduced the amount of increase in center-point thickness and central 1.0 mm subfield mean thickness after phacoemulsification in eyes of diabetic patients. Although it also reduced the incidence of CME, it had no effect on visual acuity gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 28 publications
5
29
1
3
Order By: Relevance
“…Lam et al, (2005), assessed the efficacy of phacoemulsification with 4 mg intravitreal triamcinolone injection in 19 eyes of 15 diabetic patients with cataract and diabetic macular edema with a follow-up of 6 months and found that 58.8% of eyes showed improvement in BCVA of >=2 lines (15) . Ozgur et al, (2016), Show that the BCVA during the 6 months of follow-up period after a successful PHACO surgery with 4 mg intravitreal triamcinolone injection was significantly higher than the initial BCVA (16), But Ahmadabadi et al, (2010), reported injection of triamcinolone after phacoemulsification had no effect on visual acuity (17). Anatomically, in this study, the central macular edema of patients who had phacoemulsification together with intravitreal triamcinolone injection showed reduction to a minimum CMT achieved at 6 th week and was sustained at 3 month.…”
Section: Discussionmentioning
confidence: 99%
“…Lam et al, (2005), assessed the efficacy of phacoemulsification with 4 mg intravitreal triamcinolone injection in 19 eyes of 15 diabetic patients with cataract and diabetic macular edema with a follow-up of 6 months and found that 58.8% of eyes showed improvement in BCVA of >=2 lines (15) . Ozgur et al, (2016), Show that the BCVA during the 6 months of follow-up period after a successful PHACO surgery with 4 mg intravitreal triamcinolone injection was significantly higher than the initial BCVA (16), But Ahmadabadi et al, (2010), reported injection of triamcinolone after phacoemulsification had no effect on visual acuity (17). Anatomically, in this study, the central macular edema of patients who had phacoemulsification together with intravitreal triamcinolone injection showed reduction to a minimum CMT achieved at 6 th week and was sustained at 3 month.…”
Section: Discussionmentioning
confidence: 99%
“…В то же время разницы в МКОЗ между группами обнаружено не было. Эпизоды повышения ВГД были зафик-сированы в 15% случаев в группе триамцинолона [33]. Сто-ит отметить, что триамцинолона ацетонид не имеет офици-ального разрешения для ИВИ на территории Российской Федерации и используется off-label.…”
Section: кортикостероидыunclassified
“…52 No significant differences were identified between various NSAID preparations. 53,54 Furthermore, various systemic and intraocular treatments have been used in patients with refractive PCME, unresponsive to topical NSAIDs and corticosteroids. Oral acetazolamide, in addition to topical anti-inflammatory treatment, supports the resolution of PCME.…”
Section: Treatmentmentioning
confidence: 99%
“…Previous studies have investigated the use of high frequency prednisolone eye drops, oral prednisolone, intravitreal TA, and subtenon TA. [52][53][54][55][56] The risk-benefit ratio of various dosages and routes of corticosteroid administration should be further explored, considering the efficacy and safety of topical, subconjunctival, subtenon and intravitreal corticosteroid administration.…”
Section: Prevention Of Cystoid Macular Edema In Diabeticsmentioning
confidence: 99%
See 1 more Smart Citation